Pendidikan Kesehatan Dengan Mengunakan Pemeriksaan Payudara Sendiri Dalam Mencegah Ca Mammae - Bara, Farida Tandi; Suardi, Yunita Suriani; Ilham, Radiah; Herlina, Herlina; Basir, Anastasia A.; Kurniati, Eni; Nuryani, Siti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Screening for breast cancer is finding people or groups of people who are detected as having disorders/abnormalities that may be Ca Mammary and then require a confirmation diagnosis. Screening is aimed at getting early mammary ca so that the treatment results are effective; so it will reduce the possibility of recurrence, reduce mortality and improve quality of life. Some actions for screening are Breast Self-Examination (BSE), Clinical Breast Examination (SADANIS), and Screening mammography. The method of implementing Community Service includes health education and Self-Breast Examination (BSE) for participants which is carried out at the Lumaring Village office AULA. This community service activity was carried out for 1 day. The results showed that 26 participants had high knowledge in practicing breast self-examination and 6 participants had moderate knowledge in practicing breast self-examination techniques. It is concluded that there is an influence of health education and breast self-examination (BSE) with increasing knowledge of women of childbearing age regarding breast self-examination.